Arthritic patients' views and perceptions on exercise as an adjunct treatment regime for managing their condition - Pillay, Lervasen (My University, 2016)
Introduction: Arthritic disease, presenting with a variety of joint pathologies has a myriad of treatment modalities. Treatment is dependant on various types of medication stemming from the specific diagnosis. Treatment is often supplemented with dietary changes, lifestyle related changes and exercise. Objective: This study aimed to assess the view of arthritic patients towards exercise as an adjunct treatment to medication in managing symptoms of their condition, participant’s knowledge of appropriate exercise regimes in managing their symptoms, whether or not healthcare providers prescribed exercise as a part of treatment, the different healthcare providers exercise prescription habits, the exercise modes and the outcome of the effects of exercise (subjective feeling of pain relief). Methods: A cross-sectional survey study design was used. Patients presenting at two private general practitioners and a biokineticist practices based in the southern suburbs of Johannesburg were invited to participate in this questionnaire-based study. Patients that met the inclusion criteria (those participants diagnosed with any arthritic disease with or without a co-morbid disease not contra-indicating exercise) were included in the study. Questions were developed to determine various aspects of the effect of exercise and participants’ attitudes toward exercise as an additional management tool in arthritic patients. These were all self-reported by the participant using the questionnaire. In addition, information on the type of healthcare providers prescribing exercise, exercise modes and outcomes of exercise were also gathered. Outcomes (improvements in the participants’ arthritic condition, symptoms and activities of daily living with exercise) were used as criteria for improvement. This study did not differentiate between single joint and multi joint arthritis. Results: A total of 67 participants were surveyed of which 25% were male and 73% female. The remaining two percent were unspecified. Age distribution was as follows: 60% >50 years old, 36 % were 30-50 years old and the remaining four percent <30 years of age. Most participants suffered from osteoarthritis (N=29), followed by rheumatoid arthritis (N=27), gout (N=five) and post traumatic arthritis (N=three) while the remaining participants were not specific. Exercise was advised mostly by doctors, followed by physiotherapists then biokineticists. Osteoarthritis and rheumatoid arthritis accounted for the multi-joint involvement arthritic disease. Exercise that was advised by doctors was found to be general (walking-no specifics regarding intensity and time). It was not specific enough and mostly included walking (48%). Exercise alone diminished pain (not statistically significant; p=0.18) and improved activities of daily living by 11%, while medication alone did relieve pain (p=0.034) and improved activities of daily living by 21%. Pain was measured using a numeric pain scale and activities of daily living were self-reported by the participants using the questionnaire. Observations and analysis from the study concludes that medical treatment aided by exercise will improve results in the treatment of participants with arthritic disease. The largest improvement and statistically significant finding in perceived pain relief was noted in the combination of both exercise and medication (p=0.01) with a 32% improvement in activities of daily living. Participants surveyed are of the view that exercise assists them in managing the symptoms of arthritis. Conclusions: Exercise is an important adjunctive treatment modality. Doctors were in fact advising exercise more than other healthcare providers but this advice was very non-specific. Participants were physically active (N=52) and believe that exercise can benefit them. This studies findings suggest that healthcare providers need to prescribe exercise more specific to the patient’s condition and physical capabilities. There is no “one size fits all” exercise prescription. This study adds to the knowledge base of the field in the management of arthritic disease in the southern suburbs of Johannesburg in South Africa. It is consistent with other research done in this field. Future research should be directed toward exploring further these findings and the reasons why healthcare practitioners fail to be specific in their exercise advice.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science of Medicine in Sports Medicine. Johannesburg, 2016.